Highly compact ultra-low loss polarization insensitive 1-to-2 multimode interference splitter - Xiao, Zhe (2013)
We experimentally demonstrated a highly compact 1-to-2 multimode interference splitter to achieve polarization insensitive ultra-low loss behavior. The excess loss is 0.112 dB and 0.184 dB for TE and TM mode, respectively.